Characterizing ceramics and the interfacial adhesion to resin: I - The relationship of microstructure, composition, properties and fractography Caracterização de cerâmicas e adesão à resina: I - Relação entre microestrutura, composição, propriedades e fractografia - Alvaro Della Bona (University of São Paulo, 2005)
The appeal of ceramics as structural dental materials is based on their light weight, high hardness values, chemical inertness, and anticipated unique tribological characteristics. A major goal of current ceramic research and development is to produce tough, strong ceramics that can provide reliable performance in dental applications. Quantifying microstructural parameters is important to develop structure/property relationships. Quantitative microstructural analysis provides an association among the constitution, physical properties, and structural characteristics of materials. Structural reliability of dental ceramics is a major factor in the clinical success of ceramic restorations. Complex stress distributions are present in most practical conditions and strength data alone cannot be directly extrapolated to predict structural performance. O apelo das cerâmicas como materiais odontológicos é baseado no seu peso leve, dureza alta, inércia química e características tribológicas únicas. Um dos maiores objetivos atuais das pesquisas com cerâmicas é a produção de materiais resistentes que possam oferecer uma utilização confiável para o uso odontológico. A quantificação dos parâmetros microestruturais é importante para o desenvolvimento da relação entre estrutura e propriedades. A análise quantitative da microestrutura fornece uma associação entre a composição, as propriedades físicas, e as características estruturais dos materiais. A confiabilidade estrutural das cerâmicas odontológicas é um fator importante para o sucesso clínico das restaurações cerâmicas. Distribuições complexas de estresse estão presentes na maioria das situações clínicas e, por isso, os valores isolados de resistência não podem ser diretamente extrapolados para prever a durabilidade estrutural dos materiais.